Metacognitive Skills in Learning and Pedagogy: a Systematic Review and Analysis - Pandey, Kashish (Journal of cognition and culture, 2024)
Educational frameworks aim to empower students to become self-regulated and empowered learners. They also contribute to a robust learning community through the amalgamation of metacognitive strategies in their educational system. To shed the light on the same, we conducted a systematic review of research published between 2010 and 2022 in Web of Science, PsycINFO, and Scopus databases. The review focused on two key areas: a) the application of metacognition in teaching and learning, and b) the relationship between metacognitive strategies and pedagogical approaches. Our findings highlight metacognition’s promising role in developing self-awareness, critical thinking, and cognitive facilitation within the learning environment. Additionally, the review emphasizes self-regulated learning and cognitive instruction strategies as key pathways to metacognitive regulation. We conclude by advocating for the integration of metacognitive skills development within educational systems to promote holistic learner development.